Community Participation in Preserving Minangkabau Manuscripts in Nagari Koto Padang, Dharmasraya Regency, West Sumatra - Desriyeni, Desriyeni (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
Background of the study: The background of this research is to see the participation and consistency of the surrounding community in preserving ancient manuscripts in Nagari Koto Padang. Purpose: The purpose of this research is to study and find out community participation in preserving ancient manuscripts in Nagari Koto Padang, Dharmasraya Regency, West Sumatra. Method: This study uses a qualitative method with a case study approach, data collection is done through observation, interviews, and documentation studies. Findings: From this study it can be concluded that: (1). Community participation / participation in preserving an ancient manuscript or manuscript in Nagari Koto Padang is only limited to efforts to maintain the existence of the manuscript; (2). Carry out preventive preservation by the heirs of the manuscript by maintaining the manuscript so that it is not exposed to dust, insect attack, and maintaining air temperature or humidity so that the manuscript is not damaged, and do not forget the manuscript is kept in a safe storage; in addition, script activists also carry out curative preservation by using media transfer or what is commonly referred to as digitalization, describing the contents in a manuscript, and compiling cataloging of manuscripts; and (3). In preserving a manuscript there are obstacles that are lacking funds and operational equipment from the community, and minimal community / knowledge in preserving a manuscript. Conclusion: The Dharmasraya Regency Government and the Adityawarman Museum are advised to support the preservation of ancient manuscripts (both in physical form and the information contained therein) to provide funds and training to the community in preserving ancient manuscripts in Nagari Koto Padang.